2018
DOI: 10.1080/14755610.2018.1444655
|View full text |Cite
|
Sign up to set email alerts
|

Religious/secular discourses and practices of good sex

Abstract: This article focuses on the triangulation of sexuality, religion and secularity in Dutch society by analysing two contemporary case studies. We focus on sexual experiences and practices rather than sexual identities to further understand the constructions of what constitutes 'good' sex. The empirical research is situated in the Netherlands, where the binary of religion and sexual regulation versus secularity and sexual freedom has been dominant in both public and political discourse for a long time. Exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Yet, based on respondents' stated opinions with regard to often rather narrowly defined questions, many of these studies -but not all (e.g. Maudet, 2017;Schnabel, 2016) -fall short of accounting for the more complex and multi-layered ways in which sexual values are experienced, mobilised, and expressed in everyday life (Schrijvers and Wiering, 2018). Moreover, they often uncritically use broad social categories and thereby tend to reflect and reproduce taken-for-granted ideas about 'ethnic minorities as forming separate groups that are sexually distinct' (Krebbekx et al, 2017: 651).…”
Section: An Ethnographic Comparison Of Muslim and Christian Sexual Etmentioning
confidence: 99%
“…Yet, based on respondents' stated opinions with regard to often rather narrowly defined questions, many of these studies -but not all (e.g. Maudet, 2017;Schnabel, 2016) -fall short of accounting for the more complex and multi-layered ways in which sexual values are experienced, mobilised, and expressed in everyday life (Schrijvers and Wiering, 2018). Moreover, they often uncritically use broad social categories and thereby tend to reflect and reproduce taken-for-granted ideas about 'ethnic minorities as forming separate groups that are sexually distinct' (Krebbekx et al, 2017: 651).…”
Section: An Ethnographic Comparison Of Muslim and Christian Sexual Etmentioning
confidence: 99%
“…The notion of religious agency is also given a central role in the expanding body of literature that particularly focuses on gender, religion, and sexuality (Sharma, 2012). Empirical scholarship has shown that religious women develop myriad strategies and find possibilities to embrace both religiosity and sexuality, enabling themselves to integrate their religiosity into their sexual selves (Schrijvers and Wiering, 2018). Sexual ethics and morals can thus be considered as sites of negotiation where both religious and secular norms come into play.…”
Section: Religion and Sexuality Through The Notion Of Religious Agencymentioning
confidence: 99%
“…The most important aspect was the love they shared. For women such as Jolien, it was however essential that sexual acts were performed in a monogamous relationship and for reasons of love, not lust (Schrijvers and Wiering, 2018;Sharma, 2011). Another argument not to wait, is that in order to fully know your future partner, you have to get acquainted with each other on a sexual level as well, in order to test sexual compatibility.…”
Section: Women Who Do Not Perceive Tensions Between Catholic Teaching...mentioning
confidence: 99%
“…This move has already been suggested by Bender (2012) who recommends looking for the way 'religion' manifests in everyday contexts; it has also been applied in research studying secularity and secularism as lived (Scheer, Fadil, and Johansen 2019). By focusing on the ways in which 'religion' is separated from other domains of life in daily interactions, scholars have recently begun to combine a lived religion approach with discursive approaches (Schrijvers and Wiering 2018) or, as Helena Kupari does in this special issue, with a practice approach. Developing this research agenda further can provide a fresh perspective, for instance, on how what is recognized as 'religious' intersects with other structuring categories, such as age, gender, class, and race.…”
Section: How To Go Forwardmentioning
confidence: 99%